ANTIPLATELET MEDICATIONS IN HEMODIALYSIS: A SYSTEMATIC REVIEW - Giovani, Calista; Monica Carissa, Theodora; Priska Adelin, Claudia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Vascular access failure is a common complication seen among hemodialysis (HD) patients. Antiplatelet (AP) medications are often prescribed to help reduce thrombosis and increase vascular access patency. Studies on AP agents evaluating the bleeding risk for HD patients have produced inconsistent results. We aimed to investigate the utilization of AP medications among patients who undergo hemodialysis (HD). We performed a systematic review and meta-analysis of observational studies on AP medicaations used in HD therapy. Methods: This systematic review used Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 as standards. Inclusion criteria for literature eligibility are full-text literature, written in english, and published between 2014 and 2024. Exclusion criteria used for this study were editorials, review articles and identical journal that has been published, and submissions without DOI. Literatures were collected from online reference sources like Pubmed and SagePub. Result: In the PubMed database, the results of our search brought up 23 articles, whereas the results of our search on SagePub brought up 19 articles. The results of the search conducted for the last year of 2014 yielded a total 9 articles for PubMed and 5 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion:  AP medications are given in HD patients with high cardiovascular commorbidities to increase vascular patency and prevent thrombosis. Aspirin and P2Y12 inhibitors (PI) such as clopidogrel are commonly used. AP medications might cause shortened longevity of AV access for HD patients. The benefits of AP therapy for cardiovascular protection needs to be evaluated along with its possible effect on AVG outcomes.